Faktor-faktor Penentu Keberhasilan Pencegahan Fraud Pengelolaan Dana BUMDes - Ni Komang Sumitariani; I Made Pradana Adiputra (Ekuitas: Jurnal Pendidikan Ekonomi, 2020)
This research is a quantitative research. The population in this study were all BUMDES in Buleleng Regency, amounting to 111. The sampling method was carried out by using the Slovin technique with the inaccuracy leeway level used was 5%. Then performed the proportional random sampling technique. Based on these calculations, the sample used in this study was 85 samples with 255 respondents. The data source used in this research is primary data. The data were obtained from distributing questionnaires to predefined respondents, namely supervisors, heads, and treasurers. The data analysis technique used multiple regression analysis. The results of this study indicate that organizational culture, good corporate governance, and human resource competence affect the prevention of fraud in BUMDES fund management.